Mediación didáctica de la lúdica para el desarrollo de habilidades socioemocionales y el fortalecimiento de la convivencia entre pares (2024)
Coexistence between peers is a fundamental aspect in ensuring learning in a comprehensive manner through the didactic mediation of play to strengthen the socio-emotional skills of students. That is why, in the school environment, the importance of effective didactic mediation is highlighted, which combines play and reflection, to enhance socio-emotional learning and promote favorable and respectful interactions between equals. Therefore, the purpose of this research project is to design a proposal for didactic mediation that, based on play, contributes to the development of socio-emotional skills and the strengthening of coexistence between peers. Among the supporting theories are Social Learning Theory, Ecological Theory, Theory of Moral Development, Theory of Emotional Competencies, Theory of Emotional Intelligence, Theory of Psychosocial Development, Theory of Mediated Learning Experience, Sociocultural Theory and Game theory. The methodology is based on an epistemological approach called rationalism, a rationalist-deductive paradigm, a mixed or qualitative-quantitative research approach and will be developed in three stages; the first of a theoretical nature, the second of an empirical nature and the third of a propositional nature. This work has as its study context the IED Buenos Aires and the IDDI Nueva Granada, as a population the group of teaching managers, teachers, primary school students, psycho-counselors. The contribution of this research is represented by the possibility offered to students to strengthen socio-emotional skills in order to achieve a healthy coexistence.